2013
DOI: 10.1017/nws.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Likelihoods for fixed rank nomination networks

Abstract: Many studies that gather social network data use survey methods that lead to censored, missing, or otherwise incomplete information. For example, the popular fixed rank nomination (FRN) scheme, often used in studies of schools and businesses, asks study participants to nominate and rank at most a small number of contacts or friends, leaving the existence of other relations uncertain. However, most statistical models are formulated in terms of completely observed binary networks. Statistical analyses of FRN dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Analyzing a binary network of friendship nomination but ignoring the rank information can result in misleading statistical inferences (Hoff et al, 2013). To address this concern, this study extends the order of friendship nomination to multiplex relationships and takes into account the degree to which one type of relationship is congruent with another type of relationship.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Analyzing a binary network of friendship nomination but ignoring the rank information can result in misleading statistical inferences (Hoff et al, 2013). To address this concern, this study extends the order of friendship nomination to multiplex relationships and takes into account the degree to which one type of relationship is congruent with another type of relationship.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the case of binary data, a thresholding function may be appropriate (corresponding to the probit model), and in the ordinal case the ordered probit can be considered. Hoff et al (2013) discusses additional ℓ functions which account for censoring of binary and ordinal relations when nodes are restricted on the number of relations they can send (i.e. the number of non-zero relations in a row of Y ).…”
Section: Calculation Of Node-specific Network Factorsmentioning
confidence: 99%
“…We use the fixed rank nomination likelihood introduced in Hoff et al (2013) to model the observed network ranks and restriction that at most five friends could be listed on the survey. This likelihood assumes each observed network relation r i,j is the function of an underlying (latent) continuous measure z i,j such that the following relation consistencies are satisfied: ri,j>0zi,j>0,goodbreakri,j>ri,kzi,j>zi,k,goodbreakri,j=0and studentilisted<5friendszi,j0. The first association is the function used in probit regression which assumes that if a friendship is reported, the latent friendship value must exceed a given threshold (in this case 0).…”
Section: Analysis Of Addhealth Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of models can be estimated using MLwiN. 11 Hoff et al (2012) have also recently developed a wider range of techniques for nomination networks that also estimates the covariance structures within the SRM framework. 12 Another way this can be done is to estimate a latent space model, which integrates components of the basic SRM by incorporating the decomposition of variance into the error term of a bilinear mixedeffects model.…”
Section: International Tradementioning
confidence: 99%